QUALITY AUDIT IN BANKING INDUSTRY - Tulus Suryanto (Prosiding International conference on Information Technology and Business (ICITB), 2015)
This study examines the relationship of professionalethics audittoward auditors' opinion:auditorprofessionalismand dysfunctional behavior asintervening Variable. This research was conducted at thebankingindustryfirm in Bandar Lampung and auditors asthe sample. The data was collected by using aquestionnaire. This research represents the empirical testwhich used censuc sampling. Data analysis uses SEMAmos programs. Result of hypothesis examinationindicate that from three hypothesis raised, all of itaccepted. Accepted hypothesis 1, there is a positiverelation between professional ethics audittoward auditorsopinion:, hypothesis 2, auditorsprofessionalismis asmoderated variable professional ethics audittowardauditors' opinion:. hypothesis 3, disfunctional behavior isas negative moderated variable professional ethicsaudittoward auditors' opinion.KEYWORDS: Qoality Audit, Ethics Audit ,and SEMAmos Program